Coorporate Social Responsibility (CSR): Tinjauan Teoritis dan Praktik di Indonesia - Lina Anatan (Jurnal Manajemen Maranatha, 2009)
The issue of Corporate Social Responsibility (CSR) becomes more and more crucial as the declining participation of public sector to serve community in today’s globalization era. It has triggered the growth of corporate sectors’ roles to preserving civil society. The implementation of CSR must emphasis on sustainability, embracing internal as well as external oriented policies (inside out policy). The implementation of CSR is a voluntary principle, but government is tempted to impose regulation that would force businesses to comply with CSR principles to discourage companies to pay attention on social issues. Companies which can create good shareholder values, as well as affect positively on their stakeholders (their customers, suppliers, employees, and the community at large) are regarded as companies that concern in social responsibility through value creation on triple bottom line (profit, people, and planet) which become the fundamental to the concept of CSR.